The Effect of Assertive Commitment Therapy on Medication Adherence and Quality of Life of Pulmonary Tuberculosis (TB) Patients in the Buhit Health Center Area, Samosir Regency, Indonesia - Pita Rolina Sitanggang; Jenny Marlindawani Purba; Frida Lina Tarigan; Mido Ester J. Sitorus (Community Medicine and Education Journal, 2023)
Medication adherence is the extent to which a person's behavior in taking medication is in accordance with agreed recommendations from a health care provider. The long duration of TB treatment causes many sufferers to be disobedient because they feel they are healthy and feel bored and fed up. Assertive commitment therapy is a therapy that aims to improve flexible psychological aspects or the ability to better undergo current changes. This study aimed to determine the effect of assertive commitment therapy on medication adherence and quality of life of pulmonary TB patients in the Buhit Health Center area, Samosir Regency, in 2023. Type of quantitative research with research design quasi-experimental two group pre-test posttest design. Research in Buhit Health Center, Samosir Regency, in December 2022 – June 2023. The study population was 60 pulmonary TB patients, sampling technique used consecutive sampling. The sample was divided into 2 groups, namely 30 people in the intervention group and 30 people in the control group. Data collection using MMAS-8 and WHOQOL-BREF questionnaires. Data analysis with independent t-tests. The results of the study showed that the average value of medication adherence in the intervention group was higher after participating in the ACT program (Mean=20.54, SD=4.13) compared to the value before receiving treatment ((Mean=47.37, SD=3.68). These results indicate a difference between the mean value of medication adherence in the intervention group before and after treatment (t = -193, 09; p = 0.00). The mean value of quality of life in the intervention group was higher after participating in the ACT program (Mean=78.20, SD=11.17) compared to the value before receiving treatment (Mean=42.86, SD=7.61). These results show a difference between the mean value of quality of life in the intervention group before and after treatment (t = -55,42; p = 0,00).